Exploring the Effectiveness of VR-Based Educational Games in Improving Student Engagement and Comprehension in Computer Architecture - Irfan, Dedy; Herayono, Andhika; Ayu, Fitri; Rinaldi, Rinaldi; Syafar, Syafril; Edidas, Edidas; Hanesman, Hanesman (Journal of Applied Engineering and Technological Science (JAETS), 2025)
This study examines the effectiveness of integrating VR-based educational games into the Computer Architecture Organization course to enhance students’ understanding, motivation, and overall learning experience. VR-based learning offers an immersive environment that allows students to engage interactively with complex computer architecture concepts, potentially bridging the gap between theoretical knowledge and practical application. Data were collected from 100 students through a post-test survey, focusing on three primary variables: student understanding, motivation, and effectiveness of VR games. Using Structural Equation Modeling (SEM) with SmartPLS, we analyzed the relationships among these variables. The findings indicate a significant positive effect of motivation and understanding on the perceived effectiveness of VR-based educational games, with motivation having a stronger impact. These results underscore the value of VR technology in enhancing student engagement and comprehension in technical education. This study suggests that VR gamification can be a valuable tool in modernizing educational practices, particularly in areas requiring high engagement and complex conceptual understanding.